ANTIBACTERIAL ACTIVITY OF AMORPHOPHALLUS KONKANENSIS AND AMORPHOPHALLUS BULBIFER TUBER - Shete, Chidanand c; Wadkar, Suryakant; Inamdar, Farida; Gaikwad, Nikhil; Patil, Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Evaluation of antibacterial activity of unexplored, endemic Amorphophallus konkanensis (AKT) Hett., Yadav & Patil and Amorphophallus bulbifer (ABT) (Roxb.) Bl. Methods: Acetone and ethanol extracts of tubers of AKT and ABT were evaluated for in vitro antibacterial activity against Bacillus subtilis, Micrococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Salmonella typhi, Klebsiella pneumoniae using agar diffusion method, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and growth pattern of test organisms. High-performance liquid chromatography (HPLC) analysis was carried out for active phenolic compounds. Results: AKT and ABT extracts for both solvents showed significant antibacterial activities. The zone of inhibition was ranged from 12-25 mm to 11- 23 mm for AKT and ABT extracts respectively. Highest significant activity was observed against M. aureus. The MIC values of acetone extracts were ranged from 200-350 Î¼g/ml (AKT) to, 200-400 Î¼g/ml (ABT). Ethanol extracts of AKT and ABT were showed MIC at 250-450 Î¼g/ml and 300-450 Î¼g/ ml respectively. MBC value of acetone extracts ranged from 260-460 Î¼g/ml (AKT) to 300-500 Î¼g/ml (ABT) and for ethanol extracts 340-500 Î¼g/ml (AKT) and 380-540 Î¼g/ml (ABT). The effect of extracts on growth of microorganisms was also studied. HPLC analysis showed phenolic compounds viz. tannic acid, gallic acid, quercetin, p-coumaric acid, and catechin. This polyphenolic rich extracts of AKT and ABT have demonstrated various degree of microbial growth inhibition. Conclusion: Antibacterial activity of AKT and ABT implies that, these plants have the potential for preparation of alternative medicines for infections caused by microorganisms that have become resistant to the current therapeutic measures. Keywords: Amorphophallus konkanensis, Amorphophallus bulbifer, Antibacterial activity, Minimum inhibitory concentration, minimum bactericidal concentration, High-performance liquid chromatography.